Ethiopians and Khoisan Share the Deepest Clades of the Human Y-Chromosome Phylogeny - Semino, Ornella (The American Society of Human Genetics, 2002)
The genetic structure of 126 Ethiopian and 139 Senegalese Y chromosomes was investigated by a hierarchical analysis of 30 diagnostic biallelic markers selected from the worldwide Y-chromosome genealogy. The present study reveals that (1) only the Ethiopians share with the Khoisan the deepest human Y-chromosome clades (the African-specific Groups I and II) but with a repertoire of very different haplotypes; (2) most of the Ethiopians and virtually all the Senegalese belong to Group III, whose precursor is believed to be involved in the first migration out of Africa; and (3) the Ethiopian Y chromosomes that fall into Groups VI, VIII, and IX may be explained by back migrations from Asia. The first observation confirms the ancestral affinity between the Ethiopians and the Khoisan, which has previously been suggested by both archaeological and genetic findings.